The gamut of perspectives, challenges, and recent trends for in situ hydrogels: a smart ophthalmic drug delivery vehicle. (6th August 2020) - Das, Beauty; Chattopadhyay, Dipankar; Rana, Dipak
Abstract : This review precisely elaborates the different approaches that have been explored to date for the development of ophthalmic delivery vehicles based on polymers/copolymers. Abstract : Polymers have a major role in the controlled delivery of pharmaceutical compounds to a targeted portion of the body. In this quest, a high priority research area is the targeted delivery of ophthalmic drugs to the interior regions of the eyes. Due to their complex anatomical/biochemical nature. This necessitates an advanced drug delivery cargo that could administer a therapeutic agent to the targeted location by evading various obstacles. The ongoing focus is to design an ophthalmic formulation by coupling it with a smart in situ forming polymeric hydrogel. These smart macromolecules have an array of unique theranostic properties and can utilize the in vivo biological parameters as a stimulus to change their macromolecular state from liquid to gel. The fast gelling hydrogel improves the corneal contact time, facilitates sustained drug release, resists the burst-out effect, and assists drug permeability to anterior regions. This review summarizes the rationale, scientific objectives, properties, and classification of the biologically important in situ hydrogels in the niche of ophthalmic drug delivery. The current trends and prospectives of the array of stimulus-responsive polymers, copolymers, and nanomaterials are discussed broadly. The crucial biointerfacial attributes with pros and cons are reviewed by investigating the effect of the nature of polymers as well as the ratio/percentage of additives and copolymers that influence the overall performance.